Less hepatic decompensation events but rising liver cancer in hepatitis B patients on long-term nucleos(t)ide therapy - Treviño, Ana; Soriano, Vicente (AIDS Reviews, 2023)
[Abstract not available]
Keywords: hepatic decompensation; hepatitis B; Scopus(2); JCR